GOVERNMENT GOVERNANCE INNOVATION IN REALIZING SMART VILLAGES BASED ON SOCIAL LITERACY AND EDUCATION: INOVASI TATA KELOLA PEMERINTAH DALAM MEWUJUDKAN DESA CERDAS (SMART VILLAGE) BERBASIS LITERASI SOSIAL DAN PENDIDIKAN - Victor Lumbanraja (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Advances in digital technology are driving the transformation of governance towards a smart village model. This research aims to explain the form of village government governance innovation in realizing smart villages, analyze the role of social literacy and education in supporting the success of its implementation, and identify challenges and opportunities faced in the village digitalization process. This study uses a qualitative approach with a literature study method that refers to the perspective of public governance and sociology of education. Data sources come from journal articles, books, policy documents, and research reports obtained through databases such as Google Scholar, Scopus, and DOAJ. The data were analyzed thematically and narratively. The results of the study show that village governance innovations include the digitization of public services, the use of online platforms for transparency and participation, and the formation of digital village teams. However, the success of implementation is highly dependent on social literacy and public education, especially in understanding and utilizing technology. The main challenges faced include limited infrastructure, low digital literacy, and program fragmentation between levels of government. This research recommends strengthening community literacy and multi-stakeholder collaboration as the main strategy in building inclusive and sustainable smart villages.